2020
DOI: 10.1111/iwj.13542
|View full text |Cite
|
Sign up to set email alerts
|

Onion extract gel is not better than other topical treatments in scar management: A meta‐analysis from randomised controlled trails

Abstract: To evaluate the efficacy and safety of onion extract (OE) gel on scar management, a systematic review was performed by searching Embase, PubMed, Medline, and the Cochrane Library databases, and a meta‐analysis was conducted according to Preferred Reporting Items for Systematic Reviews and Meta‐Analyses statement guidelines. Finally, 13 randomised controlled trails were enrolled for meta‐analysis. OE gel increased the total improvement scores assessed by investigators (P < .00001) and patients (P < .00001) than… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…A previous meta-analysis studied the effects of onion extract on healing, finding that onion gel increases adverse effects and has no benefit; however, onion extract in silicone gel generates improvements in healing and could be the optimal solution. Accordingly, the scientific evidence for silicone gel with herbal extracts for surgical scar enhancement is very scarce, and further research is needed to determine appropriate parameters such as doses and dosages that generate maximum benefit without harmful effects [44].…”
Section: Discussionmentioning
confidence: 99%
“…A previous meta-analysis studied the effects of onion extract on healing, finding that onion gel increases adverse effects and has no benefit; however, onion extract in silicone gel generates improvements in healing and could be the optimal solution. Accordingly, the scientific evidence for silicone gel with herbal extracts for surgical scar enhancement is very scarce, and further research is needed to determine appropriate parameters such as doses and dosages that generate maximum benefit without harmful effects [44].…”
Section: Discussionmentioning
confidence: 99%
“…In metaanalysis study, onion extract was found to be effective in scar hyperpigmentation (Ruan et al, 2019). In another meta-analysis study, although onion extract gel increases the total improvement of scar assessment, no difference was found between onion extract gel and other topical treatments (Yuan et al, 2021).…”
Section: Onion (Allium Cepa L Family Amaryllidaceae)mentioning
confidence: 98%
“…Contractubex™ consists of a mixture of Extractum capea, heparin, sodium, and allantoin. It has entered the standard treatment guidelines for the hypertrophic scars and keloids [ 9 ]. The anti-inflammatory and anti-fibrotic efficacy of this combination in epidural fibrosis and intra-abdominal adhesion models were examined and promising results were obtained [ 10 , 11 ].…”
Section: Highlight Key Pointsmentioning
confidence: 99%